Utility of renal biomarkers in early detection of cisplatin induced nephrotoxicity in male sprague dawley rats - VENKATESHA UDUPA; VEERU PRAKASH (International Journal of Pharma and Bio Sciences, 2018)
Detection of the nephrotoxicity in preclinical toxicity studies is very important in drug discovery to minimize attrition of potential candidate drug at late stage drug development. The study was undertaken to evaluate novel renal markers use in identifying acute kidney injury (AKI) compared to traditional serum biomarkers in experimentally induced nephrotoxicity in male Sprague Dawley rats. Cisplatin, a known nephrotoxicant is used at 2.5 and 5 mg/kg dose (single dose, intraperitoneal) level. On day 4 and day 8 post treatment, serum and urine samples from these rats were analysed for traditional (serum: blood urea nitrogen and creatinine, urine: protein, albumin and micro albumin (mALB) and novel biomarkers [Clusterin, kidney injury molecule-1 (Kim-1), Lipcalin-2/ Neutrophil gelatinase associated lipocalin (NGAL) and Cystatin C] and microscopic evaluation of kidneys were carried out. Urinary biomarkers were increased several folds as compared to traditional markers at both doses of cisplatin treated rats and were duration and dose dependent. Histological changes seen on Day 4 and Day 8 were of minimal to mild and moderate to severe in nature at both doses, respectively. The results indicated that the novel urinary biomarkers are sensitive than traditional biomarkers in identifying kidney damage. Renal biomarkers is useful in identifying early kidney damage and thus assessing adversity in toxicology studies. In addition, this noninvasive method is useful in diagnosing acute kidney damage in patients when the renal damage is less than 30% which is not detected using traditional biomarkers.